Diseño de un proceso efectivo de selección de personal (2016)
This investigation work is done on based on a theoric query of different authors, of whom we take concepts and definitions to use them like a support to reach our main objective: Structure a efficient Selection Process for La Organización S.A. For this were taken in account some of recognized authors in the topic like Ansorena, Alles, Saracho, Chiavenato, Mcgregor, among others. Of each of them were taken different aspects for to have a complete documentation and a guide to develop the objective. McGregor and Chiavenato were taken as the basis to understand the importance of a good Selection Process and the effects that it have on the other organizational processes. Ansorena and Alles suggest a serie of consecutive steps to do a complete Selection Process and to have more probability of success. Also was necessary to refer to the conceptualizations of Saracho, who development fundamental ideas to the understanding of the Competency-based management. For making the final proposal presented and reach the objective of this work, was used like metdology the gathering of processes because we consider it like the more appropiate for the approaching and fulfillment of our objective Among the conclusions reached are the following: currently into the company the General Manager is involved in each of one of the steps of the Selection Process, whereupon the costs of the process have increasing. The Company does not have designed a complete process in the Competency-based management that will permit that the selection be done for competencies. Grupo Salud Comportamental y Organizacional.-- Línea de Investigación: salud y trabajo.-- Área: psicología organizacional.-- Tema: diseño de un proceso efectivo de selección de personal